Relationship Between Resilience and General Health in Iranian Older Adults During the COVID-19 Pandemic - Asghar Shahbazi; Malihe Saboor; Zhale Zandieh; Samane Hosseinzadeh; Leila Miri (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives The COVID-19 pandemic was a stressful event, especially for the elderly. This study aims to determine the relationship between resilience and general health of Iranian older adults during the COVID-19 pandemic. Methods & Materials This is a descriptive-analytical study with a cross-sectional design that was conducted in 2021 on 271 older adults aged >60 years referred to the health centers in Ahar county, East Azerbaijan Province, Iran, who were selected using a random cluster sampling method. After recording their demographic characteristics, the general health questionnaire and the Connor-Davidson resilience scale were completed by them. The collected data were analyzed in SPSS software, version 23 using descriptive statistics and chi-square, Mann-Whitney U test, Kruskal-Wallis test, and Spearman correlation test. Results The mean total scores of resilience and general health were 64.38±16.42 and 24.56±10.05, respectively. There was a significant relationship between resilience and general health (r=0.25, P<0.001). There total score of resilience was higher in older adults with higher educational level (P<0.05).The general health and its dimensions of somatic symptoms and social dysfunction were higher in older adults who were living with others (P<0.05). Conclusion There was a significant relationship between resilience and general health in Iranian older adults during the COVID-19 pandemic. It is important to pay attention to these areas in them. Therefore, it is recommended to evaluate the resilience of older people during providing routine elderly care for improving their general health. It is also recommended to design appropriate educational programs during pandemics to increase resilience and general health of older adults.